Soft colloidal scaffolds capable of elastic recovery after large compressive strains - Rajamanickam, Raja; Kumar, Sushma; Kumar, Deepak; Ghosh, Shankar; Kim, Jong Chul; Tae, Giyoong; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2014)
Assemblies of inorganic or glassy particles are typically brittle and cannot sustain even moderate deformations. This restricts the use of such materials to applications where they do not experience significant loading or deformation. Here, we demonstrate a general strategy to create centimeter-size macroporous monoliths, composed primarily (>90 wt %) of colloidal particles, that recover elastically after compression to about one-tenth their original size. We employ ice templating of an aqueous dispersion of particles, polymer, and cross-linker such that cross-linking happens in the frozen state. This method yields elastic composite scaffolds for starting materials ranging from nanoparticles to micron-sized dispersions of inorganics or glassy lattices. The mechanical response of the monoliths is also qualitatively independent of polymer type, molecular weight, and even cross-linking chemistry. Our results suggest that the monolith mechanical properties arise from the formation of a unique hybrid microstructure, generated by cross-linking the polymer during ice templating. Particles that comprise the scaffold walls are connected by a cross-linked polymeric mesh. This microstructure results in soft monoliths, with moduli similar to O (10(4) Pa), despite the very high particle content in their walls. A remarkable consequence of this microstructure is that the monolith mechanical response is entropic in origin: the modulus of these scaffolds increases with temperature over a range of 140 K. We show that interparticle connections formed by cross-linking during ice templating determine the monolith modulus and also allow relative motion between connected particles, resulting in entropic elasticity.